The determinant factors of medical students' learning behavior in the national medical competency examination in Indonesia: A qualitative study - Firmansyah, Marindra; Suhoyo, Yoyo; Rahayu, Gandes Retno (Frontiers in Education, 2022)
Indonesia has applied for a national competency exit examination for medical graduates since 2014. This examination has an impact on students. There is limited literature that describes the impact mechanism of the national examination. This study aimed to identify the determinant factors of the learning behavior of medical students in the national medical competency examination during the COVID-19 pandemic in Indonesia. This qualitative study was conducted with semi-structured in-depth interviews face-to-face with thirteen medical students from the Faculty of Medicine Universitas Islam Malang and online interviews with thirteen medical students from the Faculty of Medicine Universitas Gadjah Mada, Indonesia. Theoretical sampling was done by adding three medical students from a faculty of medicine in east Indonesia. Semi-structured in-depth interviews with respondents from FK Unisma were conducted offline with strict health protocols. Meanwhile, communications with respondents from FK-KMK UGM and the eastern Indonesia medical faculty were conducted online by telephone or through Zoom meetings. Transcripted interviews were coded openly. Themes were finalized through discussion to reach a consensus. The extracted concepts from our study were classified into ten categories that describe the determinant factors of learning behavior and two categories of learning behavior. These categories include task value belief, goal orientation, weakness, impact failure, benefits of passing the exam, self-efficacy, beliefs, barriers to learning, environment factors, and test anxiety. The learning behavior itself consists of two categories; quality of learning and regulation of learning. The conclusion is determinant factors consist of internal and external factors. Internal factors include task value, goal orientation, weakness, benefits of passing the exam, self-efficacy, belief, and test anxiety. The external factor includes the environmental factor. These factors determine the medical student learning behavior in the national medical competency examination during the COVID-19 pandemic in Indonesia, both in quality and regulation of learning. The impact of failure only determines the regulation of learning, while the barrier to learn only determines the quality of learning.